Intelligent decision technologies 2016. Proceedings of the 8th KES International Conference on Intelligent Decision Technologies (KES-IDT 2016) /: Proceedings of the 8th KES International Conference on Intelligent Decision Technologies (KES-IDT 2016). Part II : (2016) - Unknown
No abstract available